"Language, " "communication, " and the longing for the authentic in LSP testing. (April 2016) - Hoekje, Barbara
This commentary argues that the OET research raises inescapable contradictions in trying to separate "language" from "communication" within a weak performance test and advocates for reconceptualizing the legitimate domain of "language" more widely, reclaiming the full potential of the communicative competence framework.